Azerbaijan's Public Finance Management: Expert Opinions on Effective Economic Policy Solutions - Ibrahim Niftiyev (Proceedings. Tekirdağ Namık Kemal University, Faculty of Economics and Administrative Sciences, 4th International Symposium on Public Finance, September 16-17, 2024, Tekirdağ, Turkey, 2024)
Public finance studies are an essential part of any country's economic analysis. Such studies play a crucial role in understanding the efficient allocation of resources, redistribution of income and macroeconomic stabilization. However, in the case of the Azerbaijani economy, there is little academic work on this topic. Considering this fact, this paper aims to provide the results of the main research project that aimed to analyze the state of academic publications on public finance management in Azerbaijan. Employing thematic analysis (TA) as the main research method, this paper reports the results of the initial analysis of the 30 structured expert interviews, who are mainly economists, government officials and private sector representatives. The first phase of the main research had a variety of directions, but this paper focuses on the secondary TA, which includes only policy suggestions to provide a more focused and detailed perspective. The findings show that the Azerbaijani government needs to continue working to increase the effectiveness of the state budget by reducing dependence on oil and gas revenues, implementing tax and structural reforms, being rational and strict in spending, adopting international standards, and focusing on more effective tax collection. In addition, the experts were not satisfied with the current state of academic studies on public finance in Azerbaijan and suggested being open and innovative in this direction in order to be better informed and prepared for the challenges of future economic cycles. The findings and interpretations of this paper will be of interest to government authorities, public institutions, academic circles and private parties, as public finance plays a crucial role in economic development and social welfare. There is a need to popularize the study of public finance using the Azerbaijani economy as an example, which requires a higher level of research interest and academic freedom.
Keywords: 330; Azerbaijani economy; expert interviews; fiscal policy; policy measures; public policy; public finance